Thoracic endometriosis syndrome: Comparison between catamenial pneumothorax or endometriosis-related pneumothorax and catamenial hemoptysis. (June 2018) - Fukuda, Shinya; Hirata, Tetsuya; Neriishi, Kazuaki; Nakazawa, Akari; Takamura, Masashi; Izumi, Gentaro; Harada, Miyuki; Hirota, Yasushi; Koga, Kaori; Wada-Hiraike, Osamu; Fujii, Tomoyuki; Osuga, Yutaka
Abstract: Objectives: To evaluate the clinical features of thoracic endometriosis syndrome (TES) represented by catamenial pneumothorax (CP), endometriosis-related pneumothorax (ERP), and catamenial hemoptysis (CH). Study design: In this retrospective study, we enrolled 25 patients with TES, 18 of whom had CP/ERP and 7 had CH, to investigate the clinical presentation, effectiveness of treatment, and recurrence rates in these disorders. Results: The age at onset was significantly lower in patients with CH than in patients with CP/ERP (P < 0.05). In 94.4% of patients with CP/ERP, pneumothorax was observed on either the right side or bilaterally, however there was no tendency toward laterality of CH among our cases. In our study, patients with CP/ERP predominantly underwent surgical management and the recurrence rate during treatment was higher in patients with CP/ERP than in those with CH. We found that the recurrence frequency of CP/ERP was lowest under the combination therapy with thoracic surgery and postoperative hormonal therapy. Conclusion: Our findings suggest that CP/ERP and CH are different pathological conditions and CP/ERP is more difficult to manage than CH.